Impact of Social Exclusion on Customer Participation in Innovation: Role of Customer-Company Identification - Hui, Zhang; Yupeng, Mou; Chenglong, Zhang; Haiqin, Li; Daomeng, Guo (Frontiers in Psychology, 2021)
In a social context, customer participation in the innovation process is often accompanied by social exclusion situations, which are generally believed to have a negative impact on individuals. However, research results and marketing practices show that social exclusion can also exert a positive influence on creativity, product selection, perceived risk, and so on. Through two experimental studies, this research explores the relationship between social exclusion and customer participation in innovation. It finds that social exclusion has a positive influence on customer participation in innovation and that customer-company identification mediates this relationship.